Cellular Responses in Human Dental Pulp Stem Cells Treated with Three Endodontic Materials. (24th May 2017) - Victoria-Escandell, Alejandro; Ibañez-Cabellos, José Santiago; de Cutanda, Sergio Bañuls-Sánchez; Berenguer-Pascual, Ester; Beltrán-García, Jesús; García-López, Eva; Pallardó, Federico V.; García-Giménez, José Luis; Pallarés-Sabater, Antonio; Zarzosa-López, Ignacio; Monterde, Manuel
Abstract : Human dental pulp stem cells (HDPSCs) are of special relevance in future regenerative dental therapies. Characterizing cytotoxicity and genotoxicity produced by endodontic materials is required to evaluate the potential for regeneration of injured tissues in future strategies combining regenerative and root canal therapies. This study explores the cytotoxicity and genotoxicity mediated by oxidative stress of three endodontic materials that are widely used on HDPSCs: a mineral trioxide aggregate (MTA-Angelus white), an epoxy resin sealant (AH-Plus cement), and an MTA-based cement sealer (MTA-Fillapex). Cell viability and cell death rate were assessed by flow cytometry. Oxidative stress was measured by OxyBlot. Levels of antioxidant enzymes were evaluated by Western blot. Genotoxicity was studied by quantifying the expression levels of DNA damage sensors such as ATM and RAD53 genes and DNA damage repair sensors such as RAD51 and PARP-1. Results indicate that AH-Plus increased apoptosis, oxidative stress, and genotoxicity markers in HDPSCs. MTA-Fillapex was the most cytotoxic oxidative stress inductor and genotoxic material for HDPSCs at longer times in preincubated cell culture medium, and MTA-Angelus was less cytotoxic and genotoxic than AH-Plus and MTA-Fillapex at all times assayed.